Analisis Penerapan Supply Chain Management Studi Kasus Pada Perusahaan Retailer - Fahmy Radhi, Endang Hariningsih, (Jurnal Bisnis Teori & Implementasi)
Objectif of this study is explore the implementation of SCM in retail companies and also its performance assessment by using the method of SCOR Level 1 customer facing aspects. The study was conducted in Matahari Department Store and Supermarket.The research was done by searching the primary and secondary data through interviews with the company participant. Â Matahari Department Store and Supermarket has SOPs to organize the integration of all the relationship with supply chain participant in supporting the business needs of consumers. Performance Level 1 customer facing aspects of the high performance delivery of components for the Jakarta area in 2011 amounted to 99, 09%, while for outside Jakarta amounted to 99,97%.Keywords:Â supply chain management, retailer, SCOR